PENGARUH EDUKASI PENCEGAHAN ANEMIA MENGGUNAKAN MEDIA POWERPOINT DAN LEAFLET TERHADAP PENGETAHUAN DAN SIKAP SAAT MENSTRUASI PADA SISWI SEKOLAH MENENGAH KESEHATAN - Rahmi Nurmadinisia (STIKes Mitra Keluarga, 2023)
Anaemia was still a global public health problem with the highest targets being young women and women of childbearing age. Based on data from the Global Nutrition Report, around 33% of female adolescent are detected with anaemia. Lack of knowledge related to anemia is one of the causes of anemia in adolescent. This research was conducted to see effect education on increasing knowledge and attitudes the female student of Puspita Medika Depok towards preventing anemia during menstruation. The research used in this study pre experimental with one group pre post design approach. The sampling technique in this study was total sampling. The number of samples in this study were 46 students. The result in this study were that were was increase in students knowledge after being given an intervention, but not in a change in attitude. There was an effect of increasing knowledge before and after the educational intervention was given, but the was no significant change in student’s attitudes when the intervention was given. However, the average attitude value was good, because it is in the middle of the two extreme point.